Impact of comorbidities and previous surgery on mid-term results of revision total knee arthroplasty for periprosthetic joint infection - Koch, Kevin-Arno; Spranz, David Maximilian; Westhauser, Fabian; Bruckner, Thomas; Lehner, Burkhard; Alvand, Abtin; Merle, Christian; Walker, Tilman (Journal of Clinical Medicine, 2023)
(1) Background: In the treatment of periprosthetic joint infection (PJI), the individual host status and previous surgical procedures appear to have a relevant influence on success rates and clinical outcome of knee revision surgery. Current data about the predictive value are limited in this subgroup of patients. (2) Methods: Retrospectively, 107 patients (109 knees) undergoing two-stage exchange knee arthroplasty for PJI using a rotating-hinge design with at least two years follow-up. The cumulative incidence (CI) for different endpoints was estimated with death as competing risk. Univariate and multivariate analyses for potential predictive factors were performed. Patient-related outcome measures (PROMs) for clinical outcome were evaluated. (3) Results: At 8 years, the CI of any revision was 29.6%, and of any reoperation was 38.9%. Significant predictors for risk of re-revision were the Charlson Comorbidity Index (CCI) and the number of previous surgical procedures prior to explanation of the infected implant. The functional and clinical outcome demonstrated acceptable results in the present cohort with a high comorbidity level. (4) Conclusions: A compromised host status and multiple previous surgical procedures were identified as negative predictors for re-revision knee surgery in the treatment of PJI. Reinfection remained the major reason for re-revision. Overall mortality was high.